Ultrastructural Study of an Atypical Case of Infertility - Ernesto Sánchez Sánchez; Carmen Tejedor Mardomingo (The Scientific World Journal)
An atypical case of infertility associated with severe sperm abnormalities is presented. A 29-year-old man with 4 years of primary infertility had no history of significant illness, and no hereditary pathology or male infertility existed in his family. Physical examination of the patient showed no pathological findings. The analyses of four semen samples showed: sperm count, 67-83 106/ml; 0% motility. The morphological analysis showed absence of flagellum, 14-16%; short-tail spermatozoa, 45-64%; coiled tails, 12-17%; and an abnormal proportion of spermatids and spermatocytes. Normal spermatozoa were found in 11-16%. Endocrine profile was found within the normal range. Testicular biopsy revealed impaired spermatogenesis. Scanning electron microscopy revealed sperm heads with intact nuclei and acrosomal regions. To our surprise, some of the stunted tails were uniflagellate. To our knowledge, this is a very uncommon case of sperm tail defect.